N-heterocyclice carbene catalyzed enolate generation from aldehydes, esters and anhydrides - Chen, Shaojin (2015)
N-heterocyclic carbenes have been proved to be powerful organocatalysts in asymmetric reactions. Despite the well established homoenolate-type addition reactions, the enolate-type reactions using efficient condition-control protocol or simple substrates are still under development. My study is mainly focused on the N-heterocyclic carbenes catalyzed enantioselective enolate reactions with various electrophiles. At the beginning, we discovered that α,β-unsaturated aldehydes undergo enolate addition with unactivated chalcones under chiral NHC catalysis, when weak bases was used instead of strong ones, as shown in appendix. The chemoselectivity between enolte and homoenolate is quite good and the desired lactones were obtained in good yields and excellent enantioselectivities. Thus, we applied this method to other electrophiles, including isatins and β-nitrostyrenes. However, the enolate intermediate was failed to be trapped by these substrates. Then, we introduced activated ester as the enolate precursor in chapter 2. Under chiral NHC catalysis, [4+2] cycloaddition of acetic esters with chalcones was realized in good yield and excellent enantioselectivity. Acetic ester shows great advantages compared to other enolate precursors, such as acetyl chloride and acetaldehyde. Then, we employed this method to other useful electrophiles, and still could not get the desired products through enolate intermediate. In chapter 3, we introduced aliphatic anhydrides as azolium enolate precursors in N-heterocyclic carbene catalysis. The Diels-Alder reaction of acetic anhydride and other 2-aliphatic anhydrides with α,β-unsaturated ketone esters was developed. Compared to the previous activated esters, aliphatic anhydrides are proved to be ideal enolate precursor because they are commerical available or easily prepared and most importantly, they have good reactivity with electrophiles. Finally, we employed this method to other electrophiles and a direct aldol reaction of acetic anhydride with isatins was developed under NHC catalysis, as presented in chapter 4. Various bioactive 3-hydroxy oxindoles could be efficiently obtained with good yield and high enantioselectivity. This work provided a new strategy for direct activation of less reactive aldol donors in carboxylic acid oxidation state without installing specific groups on carbonyl group or α carbon.